Probing the molecular and structural elements of ligands binding to the active site versus an allosteric pocket of the human farnesyl pyrophosphate synthase. Issue 5 (1st March 2015) - Gritzalis, Dimitrios; Park, Jaeok; Chiu, Wei; Cho, Hyungjun; Lin, Yih-Shyan; De Schutter, Joris W.; Lacbay, Cyrus M.; Zielinski, Michal; Berghuis, Albert M.; Tsantrizos, Youla S.
Graphical abstract Bisphosphonate chameleons that suggest a feed-back regulatory role for an allosteric pocket of the human farnesyl pyrophosphate synthase.